2016
DOI: 10.1039/c6ra17000e
|View full text |Cite
|
Sign up to set email alerts
|

Particle size effects in the selective hydrogenation of cinnamaldehyde over supported palladium catalysts

Abstract: Palladium particles of different sizes obtained directly and indirectly by various methods were studied to clarify the particle size effect in the selective hydrogenation of cinnamaldehyde (CAL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 71 publications
3
59
0
3
Order By: Relevance
“…No cinnamyl alcohol was formed, as expected, and no other products were observed in the GC traces. The difference in selectivity could be caused by the larger Pd particles in the NaBH 4 ‐reduced sample . Alternatively, the selectivity difference could be explained by support effects, which could be introduced by a change in the nature of the functional groups caused by the activation method.…”
Section: Figurementioning
confidence: 99%
“…No cinnamyl alcohol was formed, as expected, and no other products were observed in the GC traces. The difference in selectivity could be caused by the larger Pd particles in the NaBH 4 ‐reduced sample . Alternatively, the selectivity difference could be explained by support effects, which could be introduced by a change in the nature of the functional groups caused by the activation method.…”
Section: Figurementioning
confidence: 99%
“…As observed above, the Pd 1+NPs /TiO 2 synergistic catalyst present more than twice reactivity of simple Pd 1 /TiO 2 and Pd NPs /TiO 2 catalysts. According to Crook et al's work51,52 and the working mechanism of Pd 1 atoms and NPs, the size of Pd NPs and ratio of Pd NPs/ Pd 1 sites would affect the hydrogenation performance of Pd 1+NPs / TiO 2 catalyst.The universality and stability of Pd 1+NPs /TiO 2 catalysts. The high activity is also confirmed by the hydrogenation of other ketone/aldehydes(Table 1andSupplementary Figs.…”
mentioning
confidence: 99%
“…On the other hand, Pd [12,[21][22][23][24], Ni [25], Rh [26], Pt [9], Pt-Au [9] are selective for the hydrogenation of C=C to form saturated aldehyde. Literature report also shows that smaller Pd particle is selective towards C=C hydrogenation, forming HCAL, while larger Pd particle is selective towards C=O hydrogenation, forming HCOL [27]. Espro et al have also demonstrated the C=O bond selectivity of Pd-based catalysts in CAL hydrogenation under mild conditions [28].…”
Section: Introductionmentioning
confidence: 89%
“…Various attempts have been made to develop a suitable catalyst system for the selective (C=C vs. C=O) hydrogenation of CAL both in the gas-phase and in the liquid-phase [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%